Alzheimer’s Disease in the Context of an Aging Society: Challenges and Future Directions - Boral, Aleksandra; Czarnecki, Bartłomiej; Pniok, Wiktoria; Koczur, Julia; Werenkowicz, Wiktor; Kryś, Dominika; Brzoza, Joanna; Górski, Michał; Kurkiewicz, Wojciech (Journal of Education, Health and Sport, 2025)
Alzheimer’s disease (AD) remains the most prevalent form of dementia and a pressing public health concern, particularly in the context of global population aging. The pathogenesis of AD involves a multifactorial interplay of genetic, molecular, and immunological mechanisms, with amyloid-β (Aβ) and tau protein playing pivotal roles. Current pharmacological treatments provide symptomatic relief but lack disease-modifying effects. Recent advancements in anti-Aβ monoclonal antibodies such as aducanumab, lecanemab, and donanemab mark a significant shift in therapeutic strategies, although their clinical effectiveness and safety are still being carefully evaluated. Emerging therapeutic strategies, including gene therapy, tau-targeted interventions, neurostimulation techniques, and modulation of the gut microbiome, demonstrate potential but remain largely at the experimental stage, with limited or no clinical evaluation in humans to date. This review discusses the epidemiology, pathogenesis, and current as well as future directions in AD treatment. MATERIAL AND METHODS This article is based on a narrative review of recent research findings and clinical data related to Alzheimer's disease. It includes epidemiological statistics, clinical trial outcomes, and discusses both established pharmacological treatments and newly introduced therapies, such as monoclonal antibodies. The review also highlights emerging strategies, including gene therapies and novel therapeutic targets. Overall, it synthesizes current evidence to outline recent advances and identify areas for future research and development.